A three-dimensional evaluation of sella turcica in unilateral cleft lip and palate patients diagnosed with skeletal class III malocclusion - Khalil, Mohammad (My University, 2022)
Amaç: Bu çalışmanın amacı, tek taraflı dudak damak yarığına (TDDY) sahip hastalarda sella tursika'nın (ST) hacmini konik ışınlı bilgisayarlı tomografi (KIBT) görüntüleri kullanarak incelemek ve elde edilen sonuçları iskeletsel Sınıf III maloklüzyonu olan ancak TDDY bulunmayan bireylerin sonuçları ile karşılaştırmaktır. Gereç ve Yöntem: Bu çalışmada Marmara Üniversitesi Diş Hekimliği Fakültesi Ortodonti ve Radyoloji nden alınan 60 KIBT görüntüsü kullanılmış, sağlıklı ve TDDY grubu olmak üzere iki gruba ayrılmıştır. Sella tursika hacmini hesaplamak için ITK-SNAP (versiyon 3.8.0), lateral sefalometrik değerlendirme için NemoCeph yazılımı (versiyon 16.50.0) yazılımı kullanılmıştır. Bulgular: ST hacmi açısından iki grupta da cinsiyetler arası fark gözlenmemiştir. Sağlıklı kadın bireylerde ST hacmi ve Wits değeri arasında negatif bir korelasyon gözlenmiştir. TDDY grubunda ST hacmi ile Jarabak değeri arasında olumlu bir ilişki saptanmıştır. İki grupta da ST hacmi ile yaş arasında anlamlı bir ilişki gözlenmiştir. Tüm bireyler TDDY varlığı gözetmeksizin kadın ve erkek olarak gruplandığında, ST hacminin erkeklerde istatistiksel olarak anlamlı derecede daha büyük olduğu görülmüştür. Sonuç: Yaşın ST hacmi üzerinde pozitif etkili olduğu gözlenmiştir. Sınıf III maloküzyona sahip bireylerde TDDY varlığı ST hacmi açısından sağlıklı bireylerle arasında bir farklılık göstermemiştir.

Aim: The present study aims to evaluate the volume of the sella turcica (ST) in unilateral cleft lip and palate (UCLP) patients via CBCT (Cone Beam Computed Tomography) images and compares those results to non-cleft individuals diagnosed with skeletal Class III malocclusion. Materials and Methods: This study used 60 CBCT images collected from the archive of the Radiology Department at the Faculty of Dentistry, Marmara University. The patients were divided into two groups as healthy and UCLP groups. ITK-SNAP (version 3.8.0) software was used to calculate the volume of ST in the CBCT images and NemoCeph (version 16.50.0) software was used for the lateral cephalometric radiographs. Results: In terms of ST volume, no gender difference was found in either group. A negative correlation was observed between ST volume and Wits appraisal in female patients. There was a positive relationship between ST volume and Jarabak in UCLP group. A significant correlation was observed between ST volume and age in both groups. When all patients were grouped as male and female regardless of the presence of UCLP, the ST volume was found to be statistically larger in males. Conclusion: Age has a positive effect on ST volume. In patients with Class III malocclusion, the presence of UCLP did not show significant difference in terms of ST volume.
Keywords: : Sella Turcica; Angle Class III; Cleft Lip; Cleft Palate; Cone-Beam Computed Tomography; Konik Işınlı Bilgisayarlı Tomografi; Orthodontics; Ortodonti; Sella Tursika; Sınıf III; Yarık Damak; Yarık Dudak